Retention in HIV care among Southeast Asian people living with HIV: A systematic review and meta-analysis - Maulana, Sidik; Ibrahim, Kusman; Pramukti, Iqbal; Amirah, Shakira; Hartantri, Yovita (Belitung Nursing Journal, 2025)
Background: Despite the effectiveness of antiretroviral therapy (ART) in reducing HIV-related morbidity and mortality, the retention of HIV care remains suboptimal in Southeast Asia. Objective: This systematic review and meta-analysis aimed to investigate the coverage of retention in care and the likelihood factors for retention in HIV care among Southeast Asian people living with HIV, to inform targeted interventions and policy improvements. Methods: Following the Preferred Reporting Item for Systematic Review and Meta-analysis (PRISMA) guidelines, this study included observational studies reporting factors associated with retention in HIV care among Southeast Asian adults, with searches conducted in PubMed, Scopus, Cochrane Library, and CINAHL up to July 15, 2024. Demographic and clinical factors were analyzed using a random-effects model with the generalized linear mixed-effect model (GLLM) to estimate proportion and the DerSimonian-Laird method to estimate odds ratios (OR) with 95% confidence intervals (CI), assessing heterogeneity using the I² statistic. Results: Among the eleven studies with 46,480 pooled participants analyzed, the coverage of retention in care revealed a pooled proportion of 75.2% (95% CI: 66.7-82.1). Significant clinical factors associated with a higher likelihood of retention included high CD4 count (≥200 cells/mm³) (OR 2.17 (95%CI: 1.19-3.97, p = 0.01), WHO stage 3-4 (OR 2.06, 95%CI: 1.09-3.87, p = 0.02), not being on ART (OR 6.88, 95%CI: 1.89-25.06, p = 0.001), hemoglobin levels ≥10 g/dL (OR 0.50, 95% CI: 0.25-0.99, p = 0.04), and demographic factors of employment (OR 1.18, 95% CI: 1.02-1.38; p = 0.03). Other clinical factors, such as HIV stage, TB co-infection, drug abuse/substance use, and hemoglobin levels, did not significantly affect the likelihood of retention. Similarly, demographic factors such as age, gender, education, marital status, and geographic setting also showed no significant impact on likelihood retention. Conclusion: Retention in care among Southeast Asian people living with HIV was still below 95%. Clinical factors, particularly high CD4 counts, WHO stage, and the absence of ART, were likelihood factors for retention in HIV care, whereas other clinical and demographic factors studied did not show a significant impact. A universal test and treatment strategy is required to improve retention in care.